Monitoring multiple cortical regions during walking in young and older adults: Dual-task response and comparison challenges - Stuart, Samuel; Alcock, Lisa; Rochester, Lynn; Vitorio, Rodrigo [UNESP]; Pantall, Annette (Elsevier, 2019)
Performance of several tasks simultaneously (dual-tasks) is common in everyday walking. Studies indicate that dual-task walking performance declines with age together with cognitive function, but neural mechanisms underpinning deficits remain unclear. Recent developments in mobile imaging techniques, such as functional near infrared spectroscopy (fNIRS), allow real-time monitoring of cortical activity during walking. This study aimed to: 1) examine activity in motor and cognitive cortical regions when walking with a dual-task in young and older adults; and 2) determine the effect of cognition on dual-task cortical activity changes. Seventeen young (20.3 ± 1.2 years) and eighteen older adults (72.6 ± 8.0 years) performed dual-task conditions, lasting 5 min, with alternating 30-second experimental blocks. The primary outcome was cortical activity, assessed by measuring changes in oxygenated haemoglobin (HbO2) concentrations. Cortical regions of interest (ROI) included motor regions (premotor cortex (PMC), supplementary motor area (SMA), primary motor cortex (M1)), and cognitive regions (prefrontal cortex (PFC)). Cognitive domains were assessed using standard tests and accelerometers were used to extract gait features. Cortical activity increased with a dual-task in PMC, SMA and M1 but not in PFC regions across groups, with response most evident with initial task exposure. Older adults did not increase SMA activity with a dual-task to the same level as young adults. Dual-task cortical response was consistently associated with greater executive function across groups. In conclusion, both young and older adults responded in a similar manner to dual-task conditions. Dual-task walking activated multiple motor regions in both groups, but no significant change occurred for cognitive region activation. Cortical activation with a dual-task related to executive function.
Keywords: Cognition; Cortical activity; fNIRS; Older adults; Walking